2020
DOI: 10.3389/fendo.2020.00112
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin, Cholecystokinin, Signaling, and Biological Activities in Cellular Processes

Abstract: The structurally-related peptides, gastrin and cholecystokinin (CCK), were originally discovered as humoral stimulants of gastric acid secretion and pancreatic enzyme release, respectively. With the aid of methodological advances in biochemistry, immunochemistry, and molecular biology in the past several decades, our concept of gastrin and CCK as simple gastrointestinal hormones has changed considerably. Extensive in vitro and in vivo studies have shown that gastrin and CCK play important roles in several cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 171 publications
1
62
0
Order By: Relevance
“…PLTs contain copious amounts of mRNA, which may allow for PLT translational regulation and de novo synthesis of some proteins 42–44 . Comparison of the transcript profiles of RTPs and CSPs in plasma and PAS showed that the greatest differences between Day 5 RTP samples from baseline were found in transcripts directly associated with regulation of PLT apoptosis and CCKR pathways, which have been shown to influence the expression of downstream transcripts that affect cell survival, angiogenesis, and metabolic processes 45 . CCKRs, such as CCK1R and CCK2R, are coupled with G proteins 45 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PLTs contain copious amounts of mRNA, which may allow for PLT translational regulation and de novo synthesis of some proteins 42–44 . Comparison of the transcript profiles of RTPs and CSPs in plasma and PAS showed that the greatest differences between Day 5 RTP samples from baseline were found in transcripts directly associated with regulation of PLT apoptosis and CCKR pathways, which have been shown to influence the expression of downstream transcripts that affect cell survival, angiogenesis, and metabolic processes 45 . CCKRs, such as CCK1R and CCK2R, are coupled with G proteins 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the transcript profiles of RTPs and CSPs in plasma and PAS showed that the greatest differences between Day 5 RTP samples from baseline were found in transcripts directly associated with regulation of PLT apoptosis and CCKR pathways, which have been shown to influence the expression of downstream transcripts that affect cell survival, angiogenesis, and metabolic processes 45 . CCKRs, such as CCK1R and CCK2R, are coupled with G proteins 45 . The binding of CCK to CCK1R has been shown to induce mobilization of intracellular calcium and activation of protein kinase C via the phospholipase C, inositol triphosphate, and diacylglycerol pathways, respectively 45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] The basic amino acid residues on the C-terminal side of the Q-N-x-N-[K/R] peptides may affect the activity of the penta-peptide in the same way as peptide hormones to lead to the higher cell proliferative activity of GST-TPR19. Peptide hormones, such as gastrin and cholecystokinin, induce cell proliferative activity through specific receptors 24,25) ; thus, identification of the cellular receptor for MRJP3 and the penta-peptide would be important to our understanding of the mechanisms underlying the proliferative activity. Alternatively, TPRs might internalized directly as a cell penetrating peptide, since they are rich in R and K residues so that they may behave similarly to Tat peptide of human immunodeficiency virus (HIV) and penetratin.…”
Section: Discussionmentioning
confidence: 99%